The Use of Pacific Menhaden Oil and Palm Oil on Lipid Metabolism Profile in Blood Serum of Native Cockerels - Iriyanti, Ning; Zuprizal, Zuprizal; Yuwanta, T; Keman, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
Cholesterol is an important component of cell membrane, plasma lipoprotein and precursor of steroid synthesis in biologically crucial bile salt and steroid hormones. Cholesterol level in the blood exceeding the 300 mg/100 ml can result in the incident of cardiac disorder. Cholesterol, HDL (High Density of Lipoprotein), LDL (Low Density of Lipo protein) biosynthesis in the blood plasma of broiler chicken can be manipulated by the use of Pacific Menhaden Oil and Palm Oil. Therefore, The aim of the current experiment was to investigate the effect of long chain fatty acid from Pacific Menhaden Oil (PMO) and Palm Oil (PO) use in feed on the blood level of cholesterol, HDL and LDL of native cockerels. Four kinds of ration which contained different levels of PMO and PO were formulated. They were R0 (control, without PMO and PO); R1 (10% PO); R2 (10% PMO) and R3 (5% PMO and 5% PO). A total of 72 native cockerels, aged two weeks were kept in 24 pens, three cockerels in each pen. Each experimental unit were assingned at random to receive one of the four rations in completely randomized designed with six replicates. The use of PMO and PO in feed did not significantly affect (P>0.05) the concentration of cholesterol, HDL, LDL and triglyceride in the blood. Although statistically was not significantly significant, Cockerels fed R2 had the highest concentration of HDL (39.36 mg/dl) and the lowest concentration of LDL (9.10) in the blood. (Animal Production 7(2): 67-73 (2005) Key Words: Pacific Menhaden Oil, Palm Oil, Cholesterol, HDL, LDL, Triglyceride